Improving Student Learning Motivation on the Material of Respect and Obedience to Parents and Teachers by Implementing the Discovery Learning Model at SD Negeri 5 Trienggadeng - Nilawati; Yusrizan Abd (MANDAILING GLOBAL EDUKASIA, 2025)
This research aims to increase students' learning motivation in respectful and obedient materials to parents and teachers through the application of the Discovery Learning learning model. This research is a Class Action Research (PTK) which is carried out in two cycles, each including the stages of planning, implementation, observation, and reflection. The subject of the study was grade IV students of SDN 5 Trienggadeng which amounted to 20 people. Data collection techniques use observation, tests, and documentation. The results of the study showed that in the first cycle, the average student score was 73.18 with a completeness rate of 65.85%. After actions were taken in the second cycle with an improvement in the quality of the implementation of the Discovery Learning model, the average score increased to 74.54 and the completeness of learning increased to 78%. In addition, student activeness and participation have also experienced a significant increase. These findings show that the Discovery Learning model is effective in improving students' motivation and learning outcomes in Islamic Religious Education subjects, especially in materials on respect and obedience to parents and teachers. This model also helps create an active, fun, and meaningful learning atmosphere for elementary school students.